Implementasi Sistem Rekomendasi Tempat Wisata di Batu berbasis Android dan Location-Based Service menggunakan Metode TOPSIS - Jodie Rizky Hidayat; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Batu City located in East Java, Indonesia has become a top travelling destination for travelers to fill their travelling needs. Due to the increasing destination spot options in the city itself, has caused somewhat a problem for travelers to decide on which destination to choose. Entry price and distance are becoming less of a problem for traveler, as other criteria such as access, facilities, and educational experience that the site has to offer are as important for modern travelers. This application is to solve just that, while giving user the ability to receive site recommendations based on the said criteria including a Location-based service to easily guide the user to the chosen destination. The system was designed using a method known as TOPSIS (Technique For Order Preference by Similarity to Ideal Solution) with entry price, distance to the location, access, facilities, and educational experience as the list of criterias used. The system has been implemented on the Android platform. Tests such as blackbox-testing gave a 100% valid result, while algorithm validity also gave a 100% accurate result which was tested by comparing system output and manual calculation. The final test was usability testing which gave a score of 72.5 by using 10 respondents.